Analysis of Fatigue Behavior of Carbon Fiber Sucker Rods - Luo, Shaomeng (International Journal of Natural Resources and Environmental Studies, 2025)
This study modeled a carbon-fiber sucker rod using a three-layer concentric finite-element design comprising a carbon fiber core, a glass fiber interlayer, and a high-modulus glass fiber outer layer to simulate axial fatigue behavior in ANSYS under bonded reverse cyclic axial loading. The rod’s midsection demonstrated exceptional fatigue performance, reaching 6.53 × 10⁷ cycles and a damage index of ten, highlighting carbon fiber’s lightweight nature and high reliability. At the load application end, severe stress concentration caused a significant reduction in fatigue life, making that region especially vulnerable to failure. Along the rod’s radius, the central zone experienced the lowest fatigue life of about 2.15 × 10⁶ cycles and the highest damage peak around 465.9, due to complex load paths combined with concentrated stress. Conversely, the outer edge region, where carbon fiber directly bore the load, exhibited fatigue life and damage characteristics similar to those of the midsection. The study identified material anisotropy and uneven stress distribution as primary factors contributing to increased fatigue risk at both the rod ends and the central core. These findings offer essential guidance for optimizing end-connection design and laminate lay-up, supporting reliable and lightweight applications of composite sucker rods in deep-well environments.